Types of right to selfemployment in the water resources of farmer farms - Zoir Shofiev (Genius Journals, 2022)
This article gives a brief overview of the formation of the types of right of farmer farms to use water resources.
Keywords: Farmer Farming; Water Resources; Peasant Farming; Natural Objects